Quantum friction for a scalar model: Spatial dependence and higher orders - Fernandez Garcia, Aitor (2024)
We use a perturbative approach to evaluate transition amplitudes corresponding to quantum friction, for a scalar model describing an atom which moves at a constant velocity, close to a material plane. In particular, we present results on the probability density per unit time of exciting degrees of freedom on specific regions of the plane. This allows one to know spatial features of the effect which could have practical relevance, for instance, for the design of nanodevices.We show that the result of integrating out the probability density agrees with previous results for the same system.We also study the effect of including higher order terms in the perturbative calculation of the probability amplitude for quantum friction, and show that they do not alter the picture obtained from the first non-trivial order, in particular, the velocity threshold for the phenomenon to occur.